Economic Empowerment of Pemuda Muhammadiyah Through Compost Manufacturing and Marketing Training - Edi Joko Setyadi; Iwan Fakhrudin; Hardiyanto Wibowo; Alfato Yusnar Kharismasyah; Yudhistira Pradhipta Aryoko (Journal of Society, Community and Business Development, 2023)
Organic waste in Karangklesem village, Kutasari, has not been utilized optimally so that it has economic value. Utilization of the most possible and low cost is by making compost. PCPM Karangklesem Kutasari Purbalingga took the initiative to take advantage of this potential by utilizing the potential of Pemuda Muhammadiyah members to make it economically valuable and beneficial for individuals and organizations. For the compost production process and its marketing, PCPM Karangklesem Kutasari Purbalingga does not yet have human resources who are experts in producing compost fertilizer, so this is a significant obstacle. By looking at the existing problems, it is necessary to increase the abilities and skills of Pemuda Muhammadiyah of the Karangklesem Kutasari Purbalingga in managing organic waste through Training on Making and Marketing of Compost Fertilizer so that it can become an economic resource for individuals and organizations. The results of the science and technology program for the community which was carried out with training activities on the manufacture and marketing of compost fertilizer for Pemuda Muhammadiyah Karangklesem Kutasari Purbalingga , namely providing outputs in the form of increasing the abilities and skills of Pemuda Muhammadiyah Karangklesem Kutasari Purbalingga in managing organic waste into compost and increasing marketing analysis abilities and forming businesses self-sufficient PemudaMuhammadiyah Karangklesem Kutasari Purbalingga in utilizing the potential of organic waste to become compos Keywords: Compost, Marketing, Economic Value, Pemuda Muhammadiyah